2019
DOI: 10.1007/s13744-019-00740-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Preference of Chinavia erythrocnemis (Berg) (Heteroptera: Pentatomidae) on Reproductive Structures of Cultivated Plants

Abstract: Laboratory studies with the stink bug Chinavia erythrocnemis (Berg) (Hemiptera: Pentatomidae) were conducted to evaluate the effect of reproductive structures of cultivated plants, on nymph and adult performance, and adult preference. Results indicated that nymphs were able to complete the development on all plants evaluated. Nymph developmental time was significantly shorter on immature soybean pod [Glycine max (L.) Merrill], compared with immature green bean pod (Phaseolus vulgaris L.), immature siliques of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, the relatively long time of nymph development observed in this study, highly differ from what was reported for C. erytrocnemis -31 to 43 days to complete development on cultivated plants, such as soybean, Glycine max (L.) Merrill, green bean, Phaseolus vulgaris L., canola, Brassica napus L. var. oleifera, and wheat, Triticum aestivum L. (Lucini et al 2020), and from data on the similar species Chinavia pengue (Rolston, 1983) that took ca. 38 to 46 days on green beans (Matesco et al 2007).…”
Section: A B C D E F G H Imentioning
confidence: 99%
“…In addition, the relatively long time of nymph development observed in this study, highly differ from what was reported for C. erytrocnemis -31 to 43 days to complete development on cultivated plants, such as soybean, Glycine max (L.) Merrill, green bean, Phaseolus vulgaris L., canola, Brassica napus L. var. oleifera, and wheat, Triticum aestivum L. (Lucini et al 2020), and from data on the similar species Chinavia pengue (Rolston, 1983) that took ca. 38 to 46 days on green beans (Matesco et al 2007).…”
Section: A B C D E F G H Imentioning
confidence: 99%
“…oleifera (marSaro Júnior et al 2017;BianChi et al 2019). This stink bug is also observed feeding on bean, Phaseolus vulgaris L. pods (luCini et al 2020).…”
mentioning
confidence: 93%
“…Recent studies have reported arthropod species as pests in monocultures of canola (Gu et al, 2007). In Brazil, studies have been conducted to understand the possible negative effects of these arthropods in plantations (Bianchi et al, 2019;Lucini et al, 2020;. Nonetheless, no study has been conducted to date reporting the association of millipedes with canola, so that their impact on the agricultural management remains vastly unknown.…”
Section: Introductionmentioning
confidence: 99%